Psychological Impact in Covid Positive Pregnant Females - Javaid, Misbah Kausar; Khanum, Zohra; Parveen, Asia; Rashid, Aysha; Iftikhar, Mariam; Kaleem, Rameeza (Pakistan Journal of Medical & Health Sciences, 2022)
Apart from the physical effects of Covid-19, psychological effects are seen as well in the general population. In pregnant females, psychological impact leads to adverse pregnancy and neonatal outcomes. Due to limited data, the mental health of COVID-19 positive pregnant patients is not clear especially in relation to isolation in hospital, treatment, time and mode of delivery. Objective: To determine and compare frequency of anxiety and depression in pregnant women with and without COVID-19. Material and Methods: It was a comparative cross-sectional study that was conducted in the department of Obstetrics and Gynaecology, SGRH, Lahore. 60 pregnant females were enrolled and underwent nasopharyngeal swab for PCR and had HRCT to determine Covid-19 status. HADS was applied on all pregnant females to assess depression and anxiety and findings were subjected to statistical analysis. Results: The mean age, gestational age, anxiety scores and depression scores were 29.93±4.15, 31.1±6.28, 10.56±3.29 and 10.02±2.72 respectively. There were 60% Covid positive pregnant females, depression was present in 31.7% and anxiety was present in 65% females. Comparison of pregnant females with or without Covid infection in terms of depression and anxiety using independent T-test revealed that anxiety was significantly associated with Covid positive status (p=0.032), however, no significant association was seen between depression and covid status (p=0.641) (table 3). Conclusion: Covid-19 was frequently seen in pregnant females and was significantly associated with high frequency of anxiety. Depression was less commonly seen and was not significantly associated with Covid-19 infection.